The Effect of Workload and Organizational Climate on Turnover Intentions with Job Stress as an Intervening Variable in Generation Z Employees of PT. MMI Ambon Regional - Husni; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is examining effect of workload on work stress, examining effect of workload on turnover intention, examining effect of workload on turnover intention through work stress, examining effect of organizational climate on workload, examining effect of organizational climate on turnover intention, examining effect of organizational climate on turnover intention through work stress, and examining effect of work stress on turnover intention among Generation Z employees of PT. MMI (affiliated with PNM) in the Ambon region. This research employs a quantitative approach by distributing questionnaires to 213 employees, assisted by data processing using SmartPLS. The results indicate that workload positively influences work stress, workload positively influences turnover intention, workload positively affects turnover intention through work stress, organizational climate negatively impacts work stress, organizational climate don’t have significant effect to turnover intention, organizational climate negatively influences turnover intention through work stress, and work stress significantly influences turnover intention